N. U. Jayawardena, the first five decades - Jayawardena, Kumari; Moragoda, Jennifer ([Colombo] : N. U. Jayawardena Charitable Trust, 2008)
Biography of Sri Lankan Banker and legislator and the changes in the financial institutions in early decades of 20th century in Sri Lanka.
Keywords: Bankers -- Sri Lanka -- Biography; Legislators -- Sri Lanka -- Biography; Financial institutions -- Sri Lanka -- History -- 20th century